Clinical manifestations, para-clinical features and outcome of Iranian adults with respiratory syncytial virus (RSV) infection: a report from hospitalized patients - Maryam Shafaati; Abbas Shakoori Farahani; Mohammadreza Salehi; Mohammad Arabzadeh; Helya Bolouki Azari; Arman Soleimany; Maryam Edalatifard; Vahid Salimi; Alireza Abdollahi (BMC Infectious Diseases)
Abstract Background Respiratory syncytial virus (RSV) is an important cause of children’s pulmonary infections. However, there are fewer studies on RSV infections in adults. The purpose of this study was to describe the clinical manifestations, para-clinical characteristics, and outcome of RSV infection among adult patients who were referred to the Imam Khomeini Hospital Complex during the winter and spring of 2022–2023. Methods From December 21, 2022, to May 20, 2023, we conducted a cross-sectional study on hospitalized adults having positive RT-PCR results for RSV. We further assessed the clinical and para-clinical characteristics and outcomes of the RSV groups. Results We screened 1375 adults with suspected acute respiratory infections (ARIs) and confirmed RSV infections in 59 of them (4.3%). Of these, 23 patients were excluded from further analysis due to outpatient management, leaving 36 hospitalized patients with confirmed RSV infection (61.01%). The mean age of the hospitalized patients was 53.28 ± 20.37 years (range: 15–83), with a slightly higher proportion of females (52.80%) compared to males (47.20%). Dyspnea, productive cough, and fever were the most common symptoms, with a mean symptom duration of 10.50 days. Ischemic heart disease, hypertension, and liver failure were common underlying conditions. Notably, biochemical and inflammatory markers such as CRP, ESR, and LDH were significantly elevated beyond the normal range. Finally, five patients (13.9%) who received intensive care treatments died. Conclusions Although the rate of RSV infection was not high among Iranian adults, a greater proportion of patients required hospitalization (61%). There was a significant link between liver failure, an elevated INR, more than 30% bilateral pulmonary involvement, abdominal pain, longer ICU stays, and immunodeficiency cases with increased mortality from RSV infection. We suggest that RSV infection may act as a secondary factor in decompensating pre-existing liver failure, which was present in certain patients with underlying conditions, potentially leading to life-threatening consequences.